DISCUSSING VIRTUAL TOOLS THAT SIMULATE PROBABILITIES: WHAT ARE THE MIDDLE SCHOOL TEACHERS’ CONCERNS? - Savard, Annie; Freiman, Viktor; Theis, Laurent; Larose, Fançois (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
Mathematics teachers, researchers and specialists in educational technology from Quebec, Canada developed virtual tools that make interactive simulations of games of chance. These tools were presented to a group of teachers from New Brunswick through workshops and they then got to test and validate them with their students. Semi-structured interviews were conducted with groups of teachers following the experimentation with the tools. Results show an appreciation of the rich educational potential the virtual tools bring and the pedagogical scenarios that come with them. Participants suggest that working with simulators would increase students’ motivation and deepen their conceptual understanding of concepts that are otherwise hard to grasp, But they however lack professional development on how to teach probability and they need techno-pedagogical and didactical follow-ups. DISCUSSION À PROPOS DE SIMULATEURS VIRTUELS DES PROBABILITÉS : QUELLES SONT LES PRÉOCCUPATIONS D’ENSEIGNANTS DE MATHÉMATIQUES ? Notre étude exploratoire a permis à des enseignants du Nouveau-Brunswick, Canada, de tester des simulateurs virtuels de jeux de hasard développés par une équipe de techno-pédagogues, d’enseignants de mathématiques du secondaire et de didacticiens du Québec. Lors d’entretiens semi-structurés, les participants ont semblé découvrir un riche potentiel contenu dans les scénarios pédagogiques et les logiciels. Les avantages soulevés ont trait au fait d’appuyer leurs pratiques, tout en motivant les élèves et en augmentant leur compréhension de concepts autrement difficilement accessibles. Les besoins d’un accompagnement techno-pédagogique et didactique ont été également ressortis.